The Impact Of Augmented Reality And Artificial Intelligence Technologies On The Efficiency Of Decision-Making Among Saudi Red Crescent Ambulance Teams (The Review of Diabetic Studies, 2025)
This study aimed to identify the impact of augmented reality (AR) and artificial intelligence (AI) technologies on the decision-making efficiency of the Saudi Red Crescent Authority's ambulance teams. The study relied on a descriptive-analytical approach due to its suitability to the nature of the research problem. Data was collected using a standardized questionnaire designed to measure three main dimensions: speed of field response, accuracy of decisions in critical situations, and team members' satisfaction with the use of AR and AI technologies. The study sample consisted of 50 ambulance team workers, randomly selected from some of the Authority's main centers. The results showed a significant improvement in decision-making efficiency when applying AR and AI technologies. The arithmetic averages indicated higher levels of response speed and accuracy compared to traditional methods, with the greatest improvement being in decision accuracy in critical situations. The results also showed that participants' satisfaction with the use of the technologies was generally positive, although opinions varied among sample members to varying degrees. The results indicate that integrating these technologies contributes to enhancing the effectiveness of ambulance teams and increasing the reliability of their decisions, which positively impacts the quality of services and reduces response times. The study recommends expanding the application of augmented reality and artificial intelligence technologies within Saudi Red Crescent operations, while providing ongoing training programs to ensure their effective use. It also recommends conducting subsequent studies on larger samples in different regions of the Kingdom, with a focus on measuring the economic feasibility and long-term sustainability of these applications.